Application of M3 nickel-titanium files in one-time root canal therapy for the elderly patients and nursing effect evaluation (M3机用镍钛锉在老年患者一次性根管治疗中的应用及护理效果评价) - LUAN Xiaoyu (栾晓宇); LI Yuling (李玉玲); ZHANG Weihong (张卫红); WANG Qian (王倩) (中西医结合护理)
Objective To evaluate the application and nursing effects of M3 machine nickel-titanium file in one-time root canal therapy for the elderly patients. Methods Totally 160 elderly patients with chronic pulpitis who needed root canal therapy were treated with one-time root canal therapy. They were randomly divided into two groups with 80 cases in each group, including premolars and molars. In the experimental group, the root canals were prepared with M3 nickel-titanium rotary instruments (M3-Path file and M3 Pro file). In the control group, the root canals were dredged and prepared with traditional hand root canal instruments (C-file and K-file). The treatment time and postoperative pain between the two groups were compared. This paper also expounded the factors concerned by nurses about nursing before, during and after treatment. Results A shorter time of premolar and molar root canal preparation was observed in the experimental group than that in the control group (P＜0. 05). The outcome of postoperative pain assessment of the experimental group was significantly lower than that of the control group (P＜0. 05). Conclusion The use of nickel titanium file for M3 machine combined with high-quality nursing can significantly shorten the root canal preparation time and reduce postoperative pain response, showing a positive value of shortening the time required for nurses' chair cooperation, improving clinical work efficiency and making patients get more satisfactory medical services. (目的 评价M3机用镍钛锉在老年患者一次性根管治疗应用中的优势及护理效果。方法 选取临床诊断为慢性牙髓炎且需要进行一次性根管治疗的老年患者160例(患牙包括前磨牙及磨牙), 随机分为两组, 各80例。研究组使用M3机用镍钛锉(M3-Path通道锉、M3 PRO镍钛锉)疏通、预备根管, 对照组采用传统手用根管器械 (C型锉、K型锉)。对比两组的治疗时间和术后疼痛评分, 评价护理效果。结果 研究组患牙根管预备时间短于对照组, 差异有统计学意义(P＜0. 05); 研究组患者术后平均疼痛分值低于对照组, 差异有统计学意义(P＜0. 05)。结论 M3机用镍钛锉的使用与高质量的护理配合可缩短根管预备时间, 降低术后疼痛反应, 对缩短护理人员椅旁配合时间、提高临床工作效率和患者满意度具有积极意义。)